2014
DOI: 10.1556/ceugeol.57.2014.1.2
|View full text |Cite|
|
Sign up to set email alerts
|

An integrated magnetic susceptibility anisotropy (AMS) and structural geological study on Cenozoic clay-rich sediments from the Transdanubian Range

Abstract: Systematic structural and anisotropy of magnetic susceptibility (AMS) measurements were carried out on Cenozoic clay-rich deposits from the Transdanubian Range, central part of the Alcapa Unit. The aim was to improve the knowledge of the Neogene tectonic evolution of the area and of the connection of the stress field and the magnetic fabric of the sediments. The measurements of AMS revealed dominant foliation with weak lineation for Middle Eocene-Lower Miocene sediments. The directions of AMS lineation are ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…The stress fields of SIPOS-BENKŐ et al (2014), derived from the entire TR, were basically similar to those found by earlier studies (MÁRTON & FODOR 2003, FODOR 2008. The notable exceptions were the Late Miocene stress fields they assumed a change in minimal stress direction from E-W to NW-SE being coeval with a counterclockwise rotation event (Figure 1, C).…”
Section: Palaeostress Studies In the Alcapa Unitsupporting
confidence: 86%
See 2 more Smart Citations
“…The stress fields of SIPOS-BENKŐ et al (2014), derived from the entire TR, were basically similar to those found by earlier studies (MÁRTON & FODOR 2003, FODOR 2008. The notable exceptions were the Late Miocene stress fields they assumed a change in minimal stress direction from E-W to NW-SE being coeval with a counterclockwise rotation event (Figure 1, C).…”
Section: Palaeostress Studies In the Alcapa Unitsupporting
confidence: 86%
“…The combination of fault-slip and palaeomagnetic data made also a progress integrating anisotropy of magnetic susceptibility (AMS) data. SIPOS-BENKŐ et al (2014) used AMS data to infer early stage deformation and compare AMS and stress axes within the TR. AMS axes shows good correlation with one of the earliest stress axes, thus it has been proved to be successful measure for deformation in sediments.…”
Section: Studies After 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…Fault kinematics varied from normal to transtensional strike-slip (mostly sinistral oblique-slip) although it can mostly be deduced from outcrop-scale fault-slip data (e.g., Fodor 1991;Vojtko et al 2011;Sipos-Benkő et al 2014;Klučiar et al 2016). Stress calculations would suggest E -W to SE -NW tension although it is not clear if the different values indicate spatial or temporal variations (see Marko et al 1995;Fodor et al 1999;Hók et al 1999;Marko 2012;Sipos-Benkő et al 2014, Kovács et al 2015.…”
Section: Structural Backgroundmentioning
confidence: 99%
“…Stress calculations would suggest E -W to SE -NW tension although it is not clear if the different values indicate spatial or temporal variations (see Marko et al 1995;Fodor et al 1999;Hók et al 1999;Marko 2012;Sipos-Benkő et al 2014, Kovács et al 2015. The Late Miocene extensional tectonic regime with NW-SE directed Sh min persisted in the northern part of the basin up to the Middle Pleistocene.…”
Section: Structural Backgroundmentioning
confidence: 99%